Biometric Recognition 9th Chinese Conference, CCBR 2014, Shenyang, China, November 7-9, 2014. Proceedings - Sun, Zhenan; Shan, Shiguang; Sang, Haifeng; Zhou, Jie.; Wang, Yunhong; Yuan, Weiqi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 9th Chinese Conference on Biometric Recognition, CCBR 2014, held in Shenyang, China, in November 2014. The 60 revised full papers presented were carefully reviewed and selected from among 90 submissions. The papers focus on face, fingerprint and palmprint, vein biometrics, iris and ocular biometrics, behavioral biometrics, application and system of biometrics, multi-biometrics and information fusion, other biometric recognition and processing.
Face -- 3D Face Analysis: Advances and Perspectives -- Automatic Two Phase Sparse Representation Method and Face Recognition Experiments -- Pure Face Extraction from 3D Point Cloud Using Random Forest Skin Classification -- A Novel Cross Iterative Selection Method for Face Recognition -- The Methods of Modeling the Image Sets Based on MEAP and Its Application on Face Recognition -- A Novel Face Recognition Method Using Vector Projection -- Face Recognition Based on Non-local Similarity Dictionary -- Adaptive Weighted Label Propagation for Local Matching Based Face Recognition -- An Approach for Pupil Center Location Using Facial Symmetry -- Disguised Face Recognition Based on Local Feature Fusion and Biomimetic Pattern Recognition -- Thermal Infrared Face Recognition Based on the Modified Blood Perfusion Model and Improved Weber Local Descriptor -- Research of Improved Algorithm Based on LBP for Face Recognition -- A Real-Time Face Recognition System Based on IP Camera and SRC Algorithm -- Facial Expression Recognition Based on Classification Tree -- Multi-Task Learning for Face Ethnicity and Gender Recognition -- A Unified Facial Feature Point database -- A Novel Iterative Approach to Pupil Localization -- A Pose Robust Face Recognition Approach by Combining PCA-ASIFT and SSIM -- Live Face Detection by Combining the Fourier Statistics and LBP -- 3D Face Recognition by Collaborative Representation Based on Face Feature -- Fingerprint and Palm print -- Fake Fingerprint Detection Based on Wavelet Analysis and Local Binary Pattern -- Fingerprint Quality of Rural Population and Impact of Multiple Scanners on Recognition -- Fingerprint Match Based on Key Minutiae and Optimal Statistical Registration -- One-Class SVM with Negative Examples for Fingerprint Liveness Detection -- A New Approach to Palm print Mainline Restoration Based on Gaussian Distribution -- Vein Biometrics -- A Survey of Finger Vein Recognition.-Performance Evaluation of Finger Vein Verification Algorithms in PFVR2014 -- Capacity Analysis of Hand-Dorsa Vein Features Based on Image Coding -- Finger-Vein Recognition by Using Spatial Feature Interdependence Matrix Weighted by Probability and Direction -- A Database with ROI Extraction for Studying Fusion of Finger Vein and Finger Dorsal Texture -- Local Vein Texton Learning for Finger Vein Recognition -- Palm Vein Identification Based on Multi-direction Gray Surface Matching -- Iris and Ocular Biometrics -- A Brief Survey on Recent Progress in Iris Recognition -- An Effective Iris Recognition Method Based on Scale Invariant Feature Transformation -- A Fast Robustness Palm print Recognition Algorithm -- Eyelash Removal Using Light Field Camera for Iris Recognition -- Extraction and Analysis of Texture Information of the Iris Intestinal Loop -- Pupil Contour Extraction Method of Anti-light Spot Interference for Iris Image Captured in Visible Light -- Behavioral Biometrics -- Couple Metric Learning Based on Separable Criteria with Its Application in Cross-View Gait Recognition -- Enhancing Human Pose Estimation with Temporal Clues -- A Simple Way to Extract I-vector from Normalized Statistics -- A Novel and Efficient Voice Activity Detector Using Shape Features of Speech Wave -- A Robust Speaker-Adaptive and Text-Prompted Speaker Verification System -- Optimization of Pathological Voice Feature Based on KPCA and SVM -- Text-Independent Writer Identification Using Improved Structural Features -- Application and System of Biometrics -- An Effective Optical Component to Increase the Illumination Uniformity of Extended LED Light Source -- Nuclear Norm Based Bidirectional 2DPCA -- Design of an Embedded Multi-biometric Recognition Platform Based on DSP and ARM -- Standardization of Gas Sensors in a Breath Analysis System -- Multi-biometrics and Information Fusion -- Discriminative Super-Resolution Method for Low-Resolution Ear Recognition -- Multimodal Finger Feature Recognition Based on Circular Granulation -- A Multimodal Finger-Based Recognition Method Based on Granular Computing -- An Intelligent Access Control System Based on Multi-biometrics of Finger -- Other Biometric recognition and Processing Cascaded Convolutional Neural Network for Eye Detection Under Complex Scenarios -- A People Counting Method Based on Universities$1 (BSurveillance Videos and Its Application on Classroom Query -- The Study of Feature Selection Strategy in Electrocardiogram Identification -- A Novel Method for Shoeprint Recognition in Crime Scenes -- Person Re-identification with Data-Driven Features -- A Similar Interaction Model for Group Activity Recognition in Still Images -- A New Hand Shape Recognition Algorithm Unrelated to the Finger Root Contour -- An Image Thinning Processing Algorithm for Hand Vein Recognition -- Classification of Patients with Alzheimer$1 (Bs Disease Based on Structural MRI Using Locally Linear Embedding (LLE).s
Keywords: Computer science; Algorithms; Computer graphics; Image processing; Pattern recognition; Biometrics (Biology).; Computer Science; Biometrics; Pattern Recognition; Image Processing and Computer Vision; Algorithm Analysis and Problem Complexity; Computer Graphics; Information Systems Applications (incl. Internet).; Electronic books